2019
DOI: 10.1108/srj-09-2017-0191
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of corporate social responsibility disclosures of UAE national banks: a multi-perspective approach

Abstract: Purpose This paper aims to examine the determinants and extent of corporate social disclosure (CSD) by UAE national banks and to investigate the changes in CSD before, during and after the latest financial crisis. Design/methodology/approach Deductive in nature, this paper uses content analysis of annual reports of 16 UAE banks over a period of six years (2006-2011) to test eight hypotheses related to size, financial performance and other variables as potential explanatory variables of the CSD extent over di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 74 publications
(95 reference statements)
3
27
1
Order By: Relevance
“…Although the previous literature also highlights that profitability has a significant positive association with various corporate issues (Menassa and Dagher, 2019; Saha, 2019), the present study has found a negative association, which is similar to the study findings by Rahman et al (2011). It is noted that the more profit-seeking operations of corporations might be possible to inspire alternative investments for more profits.…”
Section: Discussionsupporting
confidence: 91%
“…Although the previous literature also highlights that profitability has a significant positive association with various corporate issues (Menassa and Dagher, 2019; Saha, 2019), the present study has found a negative association, which is similar to the study findings by Rahman et al (2011). It is noted that the more profit-seeking operations of corporations might be possible to inspire alternative investments for more profits.…”
Section: Discussionsupporting
confidence: 91%
“…Although empirical studies by Chih et al (2010) and Dyduch and Krasodomska (2017) did not find a significant link between corporate financial performance and CSR, studies by Roberts (1992); Haniffa and Cooke (2005); Gamerschlag et al (2010) and Menassa and Dagher (2020) found that companies are more likely to disclose CSR information when they are experiencing the relatively favorable financial performance.…”
Section: Profitabilitymentioning
confidence: 95%
“…In the literature review study, Ali et al (2017) found that determinants of CSR disclosure studies in developing countries are dominated by single-country studies, including Malaysia, Singapore, and China. For example, Baba (2017); Haniffa and Cooke (2005) are among studies that have examined the determinants of CSR disclosure in Malaysia; Hossain and Reaz (2007), Joshi and Hyderabad (2018) in India; Wang et al (2013) in China; and Menassa and Dagher (2020) in the United Arab Emirates. Unlike these studies, our study focuses on the factors driving ESG disclosure among 1244 companies in 20 Asian countries during the period 2005-2017.…”
Section: Introductionmentioning
confidence: 99%
“…Famiola and Wulansari (2019), Fombrun and Gardberg (2000) and Ullmann (1985) mentioned the essential roles of mediating variables between CSR practices and CFP rather than supported their direct relationship. The research results even contradict the Managerial Opportunism Hypothesis developed by Preston and O'Bannon (1997) that postulated the negative relationship between CSR and CFP, however, partly confirm Menassa and Dagher (2019), Waddock and Graves (1997) that CSR and CFP mutually reinforce each other through a so-called virtuous circle hypothesis. On top of that, this paper advocated the Good Management Theory which posited that good adoption of CSR domains could possibly lead employee's productivity, corporate reputation, customers' satisfaction all of which cascade to financial growth.…”
Section: Resultsmentioning
confidence: 46%
“…Du et al (2013) added that external stakeholders in turn can experience better total welfare thanks to company's strategic CSR. However, the mixed results from studies examining the connection between CSR practices and Corporate Financial Performance (CFP) occur due to differences in research methodology (Famiola and Wulansari, 2019;Margolis and Walsh, 2003;Menassa and Dagher, 2019) as well as studied context (Hofstede, 1980;Singh and Mittal, 2019) which may impact managers' attitudes towards CSR and their actions (Batool et al, 2016;Nguyen et al, 2015;Waldman et al, 2006).…”
Section: Introductionmentioning
confidence: 99%